Perancangan Alat Pengering Jagung Tipe Bed Dryer Dengan Metode VDI 2221 - Sholikhin Tri Admojo; Ferida Yuamita (Jurnal Rekayasa Proses dan Industri Terapan, 2023)
The Budi Bakti Masa Farmer Group is a farmer group in Sumberrejo Village, Tempel District, Sleman Regency, DIY. When entering the corn harvest season, farmers dry their crops with the help of sunlight. The process of drying corn is done by drying it in direct sunlight. During the rainy season, farmers find it difficult to dry their corn crops. Corn drying during the rainy season take 3-5 days or even more. The purpose of this research is to design a corn dryer that can speed up the drying process and is not dependent on the weather. The research was conducted using the Verein Deutscher Ingenieure (VDI) 2221 method. Data was collected using a questionnaire. The questionnaire used in this regard is an open and closed questionnaire. The respondents in this study were members of the Budi Bakti Masa farmer group, a total of 21 people. In designing the VDI 2221 method, there are 4 stages, namely job description, concept planning, form design, and detailed design. Based on the trial results, the corn dryer was able to dry 100 kg of rice with a moisture content of 36.3% to dry rice with a moisture content of 12% within 6 hours.